All‐polymer solar cells with over 16% efficiency and enhanced stability enabled by compatible solvent and polymer additives: Photovoltaics: Special Issue Dedicated to Professor Yongfang Li. Issue 3 (1st May 2021) - Ma, Ruijie; Yu, Jianwei; Liu, Tao; Zhang, Guangye; Xiao, Yiqun; Luo, Zhenghui; Chai, Gaoda; Chen, Yuzhong; Fan, Qunping; Su, Wenyan; Li, Gang; Wang, Ergang; et al.
Abstract: Considering the robust and stable nature of the active layers, advancing the power conversion efficiency (PCE) has long been the priority for all‐polymer solar cells (all‐PSCs). Despite the recent surge of PCE, the photovoltaic parameters of the state‐of‐the‐art all‐PSC still lag those of the polymer:small molecule‐based devices. To compete with the counterparts, judicious modulation of the morphology and thus the device electrical properties are needed. It is difficult to improve all the parameters concurrently for the all‐PSCs with advanced efficiency, and one increase is typically accompanied by the drop of the other(s). In this work, with the aids of the solvent additive (1‐chloronaphthalene) and the n ‐type polymer additive (N2200), we can fine‐tune the morphology of the active layer and demonstrate a 16.04% efficient all‐PSC based on the PM6:PY‐IT active layer. The grazing incidence wide‐angle X‐ray scattering measurements show that the shape of the crystallites can be altered, and the reshaped crystallites lead to enhanced and more balanced charge transport, reduced recombination, and suppressed energy loss, which lead to concurrently improved and device efficiency and stability. Abstract : N2200 was utilized as a polymer acceptor in PM6:PY‐IT system and produced 16.04% power conversion efficiency for this typical all‐polymer solar cell, by suitably working with 1‐chloronaphthalene. Besides, the operation stabilities (T80) of binary additive processed devices are the best among state‐of‐the‐art polymerized small molecular acceptor‐based all‐polymer solar cells.